Developing Bond Markets in APEC Toward Greater Public-Private Sector Regional Partnership - Parrenas, Julius Caesar; Sinsiri, Newin; Waller, Kenneth (ISEAS Publishing, 2005)
This conference report provides a unique overview of the development of local currency bond markets in the Asia-Pacific region and cross-border investment and issuance in these markets. It brings together insights of the region’s leading capital market regulators, private sector market players, finance and central bank officials and experts from academe and international development organizations, who have gathered together to assess the extent to which the region’s bond markets have developed, and map out a regional strategy based on public–private sector partnership that promises to address key policy reform and capacity-building issues. This report concludes that a few emerging markets in the region have made significant advances, but many others need to undertake fundamental reforms to achieve adequate market depth and liquidity and develop an enabling regulatory framework. Successfully undertaking these reforms requires intensive regional cooperation to help address obstacles in individual economies and facilitate greater cross-border activity in the region’s bond markets. Coordination is also needed to ensure the consistency of parallel initiatives being undertaken within various regional bodies, particularly APEC, ASEAN Plus Three and EMEAP, to develop a regional bond market